FEATURES, FORMS, AND METHODS OF CLUB TRAINING SESSIONS WITH SENIOR STUDENTS - Abdullaev Mehriddin Junaydulloevich (Utilitas Mathematica, 2025)
This article scientifically analyzes and substantiates the structure, features, forms, and methods of training sessions conducted with senior students engaged in athletics at general education schools. The developed author’s methodology is based on principles of physical education and general pedagogy. It includes a model for the organizational and methodological structure of athletics club sessions in schools, a sample 48-week curriculum for school athletics clubs, the physical fitness criteria required for admitting students to the athletics club, and the daily schedule of students participating in athletics clubs at general education schools.